Fetal growth evaluation by cerebellum ultrasound measurement. Study at Cayetano Heredia National Hospita - Acho Mego, Segundo (2015)
OBJECTIVE: To obtain a nomogram that relations growth curve transverse fetal cerebellum with gestational age in normal pregnant. DESIGN: cross-sectional between March and July 2000, in the Department of Obstetrics and Gynecology, National Hospital Cayetano Heredia in Lima. MATERIALS AND METHODS: 198 pregnant women between 15 and 38 weeks of normal pregnancy were evaluated. Multiple fetal biometric measurements were performed to determine the gestational age, including the transverse diameter of the cerebellum. The data underwent a program of quadratic regression to the transverse diameter of the cerebellum. RESULTS: With the determination of the transverse diameter of the fetal cerebellum ultrasound, a nomogram is obtained for gestational age, being valid for estimation (R2 = 0.9511, P <0.0005). CONCLUSIONS: The ultrasonographic measurement of the transverse diameter of the fetal cerebellum provides good information to determine the gestational age in normal pregnancy and in millimeters measures consistent with gestational age between 19 and 25 weeks.